Effects of simvastatin and rosuvastatin on RAS protein, matrix metalloproteinases and NF‐κB in lung cancer and in normal pulmonary tissues. (19th March 2013) - Falcone, D.; Gallelli, L.; Di Virgilio, A.; Tucci, L.; Scaramuzzino, M.; Terracciano, R.; Pelaia, G.; Savino, R.
Abstract Objectives In this study, we have evaluated effects of 24‐hour treatments with simvastatin or rosuvastatin on RAS protein, NF‐κB and MMP expression in LC tissues obtained from 12 patients undergoing thoracic surgery. Materials and methods Normal and lung tumour tissues obtained from each sample were exposed to simvastatin (2.5–30 μm) or rosuvastatin (1.25–30 μm) and western blot analysis was then performed. Results We documented increased expression of proteins, MMP‐2, MMP‐9 and NF‐κB‐p65 in LC tissues, with respect to normal tissues (P < 0.01). In the malignant tissues, simvastatin and rosuvastatin significantly (P < 0.01) and dose‐dependently reduced RAS protein, MMP‐2/9 and NF‐κB‐p65 expression. Conclusions In conclusion, our results suggest that simvastatin and rosuvastatin could play a role in LC treatment by modulation of RAS protein, MMP‐2/9 and NF‐κB‐p65.